Proximate compositions and bioactive compounds of edible wild and cultivated mushrooms from Northeast Thailand - Amporn Srikram; Suriyan Supapvanich (My University, 2016)
Mushrooms are known as an excellent source of nutrients including macronutrients and bioactive compounds. Nutritional values were investigated involving proximate analysis, total antioxidant capacity (TAC), total phenol content (TPC) and total flavonoid content (TFC) of 10 edible wild mushroom species—Amanita calyptroderma Ark. et al., Amanita princeps Corner et Bas, A., Astraeus odoratus, Heimiella retispora (Pat. et. Bak.) Boedijn., Mycoamaranthus cambodgensis (Pat.) Trappe, Russula alboareolata Hongo, Russula cyanoxantha Schaeff.ex.Fr., Russula emetic (Schaeff. ex Fr.) S.F.Gray., Russula virescens (Schaeff.) fr., Termitomyces clypeatus Heim—and five cultivated mushroom species—Auricularia auricula-judae, Lentinus polychrous Lev., Lentinus squarrosulus Mont., Pleurotus sajor-caju (Fr.) Sing, Volvariella vovacea (Bull. Ex.Fr.) Sing. From the proximate analysis, the moisture contents of both wild and cultivated mushrooms ranged from 84.15% fresh weight (FW) to 90.21% FW. The ash, crude protein, fat, crude fiber and carbohydrate contents of both wild and cultivated mushrooms were in the dry weight ranges 2.56–13.96%, 11.16–50.29%, 1.43–21.94%, 2.11–38.11% and 9.56–59.73%, respectively, and the contents of macronutrients in the mushrooms varied by variety. Wild mushrooms had a high fiber content compared to cultivated mushrooms. The contents of biologically active compounds of both wild and cultivated mushrooms also varied depending on the variety. Values for the TAC, TPC and TFC of wild mushrooms were higher than those of cultivated mushrooms. In conclusion, the proximate analysis for both wild and cultivated mushrooms was variety dependent and wild mushrooms contained a higher fiber content and more biologically active compounds than cultivated mushrooms.
Keywords: Lentinus; Pleurotus; Proximate; Edible mushroom; Russula; Fungal Biology and Applications